Exploring a social-linguistic construction of Chinese students’ disciplinary identities in the mediated process of group membership affiliation in a UK-based university in China - Zhang, Jing (2017)
For the dynamic construction of Chinese students’ disciplinary identities in transnational institution, the roles of language and context in constructing multiplicity of identity remain unexplored. Based on the social and linguistic studies on identities construction, this study proposes the idea of group membership affiliation: a multi-faceted meaning-making process that mediates the relation between individual and context, in which the individual uses language to habitually engage in activities, construe positive imagination of the community and align her or himself with the other members in the groups and so gain membership. Systemic Functional Linguistics, Sociocultural theory, social identity theory and Hyland’s (2012) idea of proximity provide the theoretical and analytical frameworks for the study. The research applies an integrated methodology, drawing on lexicogrammatical and discourse-semantic approaches, as well as small amount of qualitative case study data.